Linux Bible, 10th Edition - Negus, Christopher (Wiley, 2020)
The industry favorite Linux guide Linux Bible, 10th Edition is the ultimate hands-on Linux user guide, whether you're a true beginner or a more advanced user navigating recent changes. this updated tenth edition covers the latest versions of Red Hat Enterprise Linux (RHEL 8), Fedora 30, and Ubuntu 18.04 LTS. It includes information on cloud computing, with new guidance on containerization, Ansible automation, and Kubernetes and OpenShift. With a focus on RHEL 8, this new edition teaches techniques for managing storage, users, and security, while emphasizing simplified administrative techniques with Cockpit. Written by a Red Hat expert, this book provides the clear explanations and step-by-step instructions that demystify Linux and bring the new features seamlessly into your workflow. This useful guide assumes a base of little or no Linux knowledge, and takes you step by step through what you need to know to get the job done. Get Linux up and running quickly Master basic operations and tackle more advanced tasks Get up to date on the recent changes to Linux server system management Bring Linux to the cloud using Openstack and Cloudforms Simplified Linux administration through the Cockpit Web Interface Automated Linux Deployment with Ansible Learn to navigate Linux with Amazon (AWS), Google (GCE), and Microsofr Azure Cloud services Linux Bible, 10th Edition is the one resource you need, and provides the hands-on training that gets you on track in a flash.